Characteristics of Luting Cements in the Selection of Cementation Materials for Fixed Partial Dentures: A Narrative Review - Alya, Ainun; Rais, Sri Wahyuningsih; Kesumaputri, Bebbi Arisya; Mozartha, Martha (Journal of Syiah Kuala Dentistry Society, 2025)
Background: A Fixed Partial Denture (FPD) is a permanent prosthesis cemented to abutment teeth using luting cement. One of the most common complications is retention loss, which is closely related to the type and properties of the cementation material used. Objective: This narrative review aims to analyze the characteristics of luting cements to determine the ideal material for cementing FPDs. Methods: A literature review was conducted using articles from PubMed, ScienceDirect, and Google Scholar databases published within the last 15 years. Inclusion and exclusion criteria were applied, and the selected studies were assessed for bias using the Checklist for Reporting In-vitro Studies (CRIS). Results: A total of 21 in vitro studies were reviewed. Sixteen studies reported that resin cement has the highest retention. Ten studies supported the use of zinc phosphate (ZP), zinc polycarboxylate (ZPC), glass ionomer cement (GIC), and resin cement for all-metal FPDs. Six studies favored resin cement for all-ceramic FPDs, while four studies showed positive outcomes using resin cement for porcelain-fused-to-metal (PFM) FPDs. Conclusion: Resin cement demonstrates superior retention characteristics, making it the ideal luting agent for FPDs. ZP, ZPC, and GIC also provide good performance for all-metal FPDs. In contrast, resin-modified glass ionomer cement (RMGIC) shows inferior retention and is less recommended for FPD cementation.